Sardinella ventura n. sp. (Actinopterygii: Clupeiformes: Clupeidae), a new sardine from Mauritius - Hata, Harutaka; Motomura, Hiroyuki (Zootaxa, 2021)
The new sardine Sardinella ventura n. sp. (Teleostei: Clupeiformes: Clupeidae) is described on the basis of 10 specimens collected from Mauritius. The new species is most similar to Sardinella dayi Regan 1917 in having non-deciduous scales with pores and discontinuous striae, a dark spot on the dorsal-fin origin, the pelvic fin with 8 rays, and similar number of gill rakers, in addition to very similar numbers of keeled scutes. However, the new species is distinguished from S. dayi by having a shorter caudal peduncle [6.2–7.6% SL (mean 7.0%) vs. 8.2–12.0% (9.2%) in S. dayi], larger eye [8.4–9.9% (9.0%) vs. 6.8–8.0% (7.4%)] and orbit [9.6–12.3% (10.7%) vs. 8.5–10.2% (9.3%)], longer pectoral [21.0–22.7% (21.5%) vs. 17.0–21.0% (19.8%)] and pelvic fins [12.5–13.5% (12.8%) vs. 10.4–12.2% (11.2%)], and a greater numbers of pseudobranchial filaments [17–19 (modally 17) vs. 18–22 (19)], lateral scale rows in longitudinal series [41–43 (41) vs. 38–42 (40)] and transverse scales [11 or 12 (12) vs. 11]. There were significant differences in seven meristic and 14 morphometric characters between the two species.